2019
DOI: 10.4097/kja.19195
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical performance of i-gelⓇ and Baska MaskⓇ during laparoscopic cholecystectomy

Abstract: The supraglottic airway device (SAD) is an appropriate alternative to tracheal intubation because of its advantages such as stable hemodynamics and decreased airway morbidity. It also helps to maintain adequate ventilation in laparoscopic surgery, with increased peak airway pressure (PAP) under general anesthesia [1,2]. The i-gel Ⓡ (Intersurgical Ltd., UK) is widely used for laparoscopic surgeries [1,3-5]. However, the Baska Mask Ⓡ (Logikal Health Products PTY Ltd., Australia), first introduced in 2012, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
3
16
1
Order By: Relevance
“…A few studies have highlighted the superiority of certain parameters of the Baska mask over the . However, other parameters, such as insertion time, fibre-optic view of the glottis, the use of airway manipulation, heart rate, mean arterial pressure, PAP, lung compliance, and perioperative complications, were comparable [14]. A study by Kara et al showed that the Baska mask provided a significantly higher PAP than the i-gel (15.8 cm H 2 O ± 0.9 cm H 2 O and 14.9 cm H 2 O ± 1.7 cm H 2 O, respectively) [11], which was supported by our study.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A few studies have highlighted the superiority of certain parameters of the Baska mask over the . However, other parameters, such as insertion time, fibre-optic view of the glottis, the use of airway manipulation, heart rate, mean arterial pressure, PAP, lung compliance, and perioperative complications, were comparable [14]. A study by Kara et al showed that the Baska mask provided a significantly higher PAP than the i-gel (15.8 cm H 2 O ± 0.9 cm H 2 O and 14.9 cm H 2 O ± 1.7 cm H 2 O, respectively) [11], which was supported by our study.…”
Section: Discussionmentioning
confidence: 88%
“…Kara et al conducted a comparison study between the Baska mask and i-gel in 200 patients undergoing urologic surgery. The i-gel showed significantly shorter median insertion time than the Baska mask (7 s [5][6][7][8][9][10][11][12] and 14 s [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], respectively). However, there were no significant differences in the other parameters (the number of device placement attempts, sealed pressure and the number of post-operative complications) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Both BM and LMA-P are supraglottic airway devices with an in-situ gastric channel. It is well-known that LMA-P has higher seal pressures than i-gel, and BM also has higher seal pressure than i-gel [ 12 , 13 ]. The higher seal pressure of LMA-P may be due to the additional posterior cuff; however, BM lacks any such cuff.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this device during positive pressure ventilation has been shown. [ 5 6 ] However its effectiveness in protecting the lower airway from contamination during nasal surgeries has not yet been investigated. We hypothesised that the BM is non-inferior to the Tracheal tube in preventing tracheal contamination during nasal surgeries and aimed to study the effectiveness of BM for nasal surgeries.…”
Section: Introductionmentioning
confidence: 99%